Reflexiones sobre el papel de la contextualización en la enseñanza de ciencias - Souza, Karina Aparecida de Freitas Dias de; Cardoso, Arnaldo Alves [UNESP] (My University, 2010)
The contextualization and discussion about the science role in the social and economical development are unquestionably important for the science teaching process. It doesn’t mean, however, that the scientific-theoretic knowledge and the strategies involved in its construction and application might be neglected. In this way, a dangerous situation is created when the contextualization is assumed as a unique and primordial target in science education. This paper presents a research carried out with 15 future chemistry teachers and the results show a worrying «supervalorization» of the contextualization beside other equally important aspects of the chemical knowledge.

La importancia de la contextualización y de la discusión del papel de la ciencia en el desarrollo social y económico es innegable para la enseñanza de las ciencias. Sin embargo, esto no debe significar una negligencia ni del conocimiento teórico ni de las estrategias que forman parte de su construcción y aplicación. Así, se dibuja un peligroso cuadro cuando se asume la contextualización como el único y primordial objetivo de la educación científica. Este artículo presenta un estudio realizado con 15 alumnos del último año de la carrera en Docencia de Química, cuyos resultados evidencian una preocupante «supervaloración» de lo cotidiano en detrimento de otros aspectos igualmente importantes del conocimiento químico.
Keywords: Teacher´s training; contextualization; scientific literacy; epistemology; science teaching